Modeling of the deformed state of the screen box of a heavily loaded vibratory machine - Popolov , D. V.; Shved , S. V.; Zaselskyi , I. V.; Velitchenko , V. L. (Theory and Practice of Metallurgy, 2026)
The paper addresses the problem of improving the technical and economic efficiency of heavily loaded vibratory machines through optimization of the load-bearing frame of the screen box. The main elements providing the spatial stiffness of the box structure are tubular transverse tie-beams, which operate under conditions of intensive cyclic bending loads. Analysis of the available literature indicates that these elements belong to the most highly loaded and vulnerable structural components, for which fatigue failure is the dominant failure mechanism. The traditional approach to increasing the strength of structural elements, namely, enlarging the cross-sectional area, leads to an increase in the mass of the screen box and the associated inertial loads, which adversely affects the dynamic characteristics of the vibratory machine. The objective of this study was to improve the structural efficiency of the screen box of a vibratory machine by optimizing the geometry of the tie-beams using a rational material distribution along the length of the element. An approach is proposed that involves varying the outer diameter of the tubular tie-beam according to a parabolic law while maintaining a constant inner diameter. Such an approach makes it possible to reduce the beam mass in regions of low bending moments while simultaneously maintaining or increasing stiffness in the most heavily loaded sections. To evaluate the effectiveness of the proposed solution, a series of numerical experiments was carried out using the finite element method. The simulations included calculations of axial compression, bending under transverse inertial loading, determination of the first natural frequency, and estimation of the critical buckling load for tie-beams with both baseline and parabolic profiles. The obtained results demonstrate that the use of a parabolic profile makes it possible to reduce the mass of the tie-beam by 41%, while the transverse acceleration corresponding to the onset of yielding increases by 55%, and the first natural frequency increases by 18%. Stress distribution maps indicate a more uniform loading of the material in the tie-beam with the parabolic profile. The deformed state of the screen box was also modeled using both the baseline and the optimized tie-beams. The results show that the change in beam geometry has virtually no effect on the dynamic characteristics of the box. The first natural frequency of the structure changes only slightly, while the deformation pattern and the maximum displacement amplitude remain practically unchanged. The obtained results confirm the prospects of applying variable-section tie-beams for improving the energy efficiency and reliability of vibratory machines.